EUROPEAN INTEGRATION CHALLENGES AND THEIR IMPACT ON THE INTERNATIONAL INVESTMENT MARKET IN THE CONTEXT OF ENSURING CRIMINOLOGY SECURITY (Bulletin of criminological association of Ukraine, 2023)
It has been proven that the impact of European integration challenges on the international investment market is expressed in the following aspects: 1) it causes the modernization of subjects of economic and financial relations in accordance with the requirements of the European community, which makes it possible to determine new vectors of development and movement of international investments; 2) European integration processes ensure the economic and financial stability of states as one of the subjects of the international investment market due to the European Union's support for future members; 3) European integration extends to new subjects of the international investment market the effect of a complex, all-European mechanism of regulation and control in the economic and financial dimension.It was found that the international investment market is a combination of several components, namely: subjects of investment activity, investment products, regulatory mechanisms, the result of investment activity. Each element is a completely independent category both in economic and financial and legal terms, because it plays an appropriate role in the world economic system and has a normative reflection.
Keywords: investment activity; investment market; international investment market; European integration; European integration processes; international investments.